Why having a Maximum Retail Price on a Product is a Socialist Idea and Bad for the Indian Economy? - Adityawardhan Gaikwad (International Journal of Engineering and Management Research, 2022)
In a capitalist society, the market uses the rules of supply and demand to set prices. For instance, a firm that wants to make money would raise prices as the demand for coffee rises. Tea growers would face reduced pricing and a decrease in overall production if society's taste for the beverage decreased simultaneously.